2019
DOI: 10.1001/jamainternmed.2018.5124
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Trends in Unstable Angina Diagnosis Codes for Outpatient Percutaneous Coronary Interventions

Abstract: Search trends are only proxies for engagement, and sentinel surveillance (such as surveys) will clarify these early findings. However, our findings demonstrate the power of grassroots movements to respond to large-scale public health crises. These results suggest that #MeToo may have reduced the stigma of sexual harassment and/or assault as more seek help. 5 Public health investments in preventing sexual harassment and/or assault is disproportionately small compared with the scale of the problem, 6 in part bec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 10 publications
(26 reference statements)
1
18
0
Order By: Relevance
“…The findings of this study support three out of the four hypotheses we proposed (i.e., prominent decline in [7][8][9][10][11][12]. Using the Truven MarketScan data, one study indicated that the proportion of patients coded as having higher anesthesia risks increased from 11.6% in 2005 to 18.9% in 2013 for outpatient gastrointestinal endoscopy procedures [11].…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…The findings of this study support three out of the four hypotheses we proposed (i.e., prominent decline in [7][8][9][10][11][12]. Using the Truven MarketScan data, one study indicated that the proportion of patients coded as having higher anesthesia risks increased from 11.6% in 2005 to 18.9% in 2013 for outpatient gastrointestinal endoscopy procedures [11].…”
Section: Discussionsupporting
confidence: 82%
“…A study used the Healthcare Cost and Utilization Project state databases also revealed that the proportion of outpatient percutaneous coronary interventions coded for acute indications increased prominently in New York (from 0.6% in 2010 to 8.3% in 2014), and the increase was due to a substantial rise in the number of coded unstable angina after the appropriate use criteria for coronary revascularization were released in 2009. The authors suggested the possibility of physicians increasingly classifying patients with stable chest pain as unstable angina in the outpatient setting [12].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, operationally defined CVD may be incorrectly coded. Unstable angina is one of the most up-coded conditions [52], and there is also the possibility that patients with multiple CVD could be down-coded should the doctor not have recorded all ICD codes for multiple complex conditions. However, the operational diagnosis was validated and had been widely used in previous studies [53,54].…”
Section: Discussionmentioning
confidence: 99%
“…The benign end of the spectrum exists because the boundary between diagnostic categories is blurred, with many patients fitting two or more categories. A similar analysis has identified a dramatic rise in the volume of outpatient PCI that was categorised as 'acute' following AUC 10 . The National Cardiovascular Data Registry provides an undemanding definition of 'unstable angina' which is simple to fulfil 11 .…”
Section: Is This Upcoding?mentioning
confidence: 86%